2017
DOI: 10.1038/s41467-017-02212-w
|View full text |Cite
|
Sign up to set email alerts
|

CTCF driven TERRA transcription facilitates completion of telomere DNA replication

Abstract: Telomere repeat DNA forms a nucleo-protein structure that can obstruct chromosomal DNA replication, especially under conditions of replication stress. Transcription of telomere repeats can initiate at subtelomeric CTCF-binding sites to generate telomere repeat-encoding RNA (TERRA), but the role of transcription, CTCF, and TERRA in telomere replication is not known. Here, we have used CRISPR/Cas9 gene editing to mutate CTCF-binding sites at the putative start site of TERRA transcripts for a class of subtelomere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…30 Besides, CTCF has been reported to serve as a transcription activator of genes. 31,32 In this study, CTCF was confirmed to bind with the HOXA11-AS promoter in PCa.…”
Section: Discussionsupporting
confidence: 57%
“…30 Besides, CTCF has been reported to serve as a transcription activator of genes. 31,32 In this study, CTCF was confirmed to bind with the HOXA11-AS promoter in PCa.…”
Section: Discussionsupporting
confidence: 57%
“…In future experiments, it will be important to investigate whether depletion of TERRA-MS2 transcripts results in DNA damage at the MS2-tagged telomere. Indeed, recent evidence indicates that TERRA expression facilitates replication in cis of the TERRA transcribing telomere [20], thus single-telomere TERRA downregulation may perturb DNA replication at the TERRA-depleted telomere, resulting in DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…RNA fluorescence in-situ hybridization (FISH) and live-cell imaging analyses have shown that a subset of TERRA transcripts localizes with human telomeres [5,6,17]. At telomeres, TERRA molecules have been proposed to mediate several important functions, including regulation of heterochromatin formation [16], recruitment of chromosome end-processing and chromatin remodelling factors to dysfunctional telomeres [18,19], sustaining telomeric DNA replication [20], participating in telomere length homeostasis by regulating telomerase activity [13,14] or promoting homologous recombination among telomeres through formation of RNA-DNA heteroduplex (R-loops) at chromosome ends [21-24]. In addition to their preferential association with telomeres, recent evidence indicates that TERRA transcripts interact with numerous internal chromosomal regions to regulate widespread gene expression [25].…”
Section: Introductionmentioning
confidence: 99%
“…The binding of TERRA to telomeres in cis is supported by several lines of evidence in yeast as well as in human cells . Therefore, identifying the telomeres that transcribe TERRA should inform us which telomeres are potentially capable of generating TRLs.…”
Section: Telomere R‐loops In Mammalsmentioning
confidence: 96%